Long‐term swallowing after chemoradiotherapy: Prospective study of functional and patient‐reported changes over time. (26th June 2015) - Frowen, Jacqui; Drosdowsky, Allison; Perry, Alison; Corry, June
ABSTRACT: Background: This prospective study evaluated long‐term swallowing outcomes and associated risk factors 5 years postchemoradiotherapy for head and neck cancer. Methods: Following an earlier study of 69 patients, 39 patients had patient‐reported activity and quality of life (QOL) data collected. Twenty‐one patients also underwent a videofluoroscopy swallowing study (VFSS). Results: Between 6 months and 5 years posttreatment, patient‐reported activity for solid foods significantly improved ( p < .001), returning to pretreatment levels for 74% of patients. On VFSS, swallowing function for semisolids declined, with 5 patients demonstrating a clinically significant deterioration. Factors that predicted poorer long‐term swallowing were the same as at 6 months, with the addition of older age and disease stage. Conclusion: Although long‐term patient‐reported activity improves and swallowing‐related QOL is high, up to 24% of patients may demonstrate a clinically significant deterioration in swallowing function at 5 years posttreatment. This divergence suggests a degree of adaptation that patients develop, which warrants further investigation. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E307–E315, 2016